1995
DOI: 10.1111/j.1432-1033.1995.887_a.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Structural Organization and Thermal Stability of two Spermadhesins

Abstract: The CUB domain is a widespread 1 lO-amino-acid twdule lound in fiinclionally diverse, often developmentally regulated proteins, for which an antiparallel P-b:itrel topology similar to that in irriniunoflobulin V domains has been predicted. Spemxidhesins have becn proposed as a subgroup of this protein family built up by B single CUB domain architccturc. To tcst the proposed structural model, wc have analyzed the structural organkition o f two meinher.; of the spei-madhesin protein frimily, porcine seminal plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…Control experiments were run in parallel at 7 mM Mg 2ϩ in the initial equilibration buffer. Circular Dichroism-The far-UV CD spectra of tubulin (1-5 M, equilibrated in PEDTA with 1 mM nucleotide and a known amount of Mg 2ϩ ) were acquired in a JASCO J720 dichrograph equipped with a temperature regulated cell holder (1,35), with a 0.1-cm cell at 20 Ϯ 1°C. Thermal denaturation was monitored following the variation in ellipticity at 220 nm, using a temperature scan rate of 0.5°C⅐min…”
Section: Methodsmentioning
confidence: 99%
“…Control experiments were run in parallel at 7 mM Mg 2ϩ in the initial equilibration buffer. Circular Dichroism-The far-UV CD spectra of tubulin (1-5 M, equilibrated in PEDTA with 1 mM nucleotide and a known amount of Mg 2ϩ ) were acquired in a JASCO J720 dichrograph equipped with a temperature regulated cell holder (1,35), with a 0.1-cm cell at 20 Ϯ 1°C. Thermal denaturation was monitored following the variation in ellipticity at 220 nm, using a temperature scan rate of 0.5°C⅐min…”
Section: Methodsmentioning
confidence: 99%
“…Circular dichroism spectroscopy. Circular dichroism spectra were recorded in a JASCO J-720 spectropolarimeter fitted with a thermostated cell holder and interfaced to a thermostatic bath as previously described (MenCndez et al, 1995). Farultraviolet and near-ultraviolet spectra were recorded in 0.1 -cm pathlength quartz cells at a protein concentration of about 0.15 mg/ml and 0.7 mg/ml, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…asymmetric unit. Previous biophysical studies suggested that aSFP is a homodimeric protein (MenCndez et al, 1995). However, because the crystallographic data can not rule out the possibility that aSFP crystallized as a dimer with internal crystallographic symmetry, determination of the molecular mass of aSFP was performed by analytical ultracentrifugation.…”
Section: Drr(i) = C ( L I ( K ) -( I ) L ) / E I ( K ) Where I mentioning
confidence: 99%
“…Both subunits of the spermadhesin PSP-I/PSP-I1 heterodimer are glycoproteins and have basic isoelectric points (8.0-8.6), whereas aSFP is an acidic nonglycosylated protein (PI 4.8) (Einspanier et al, 1991). In addition, thermal unfolding of aSFP has a transition temperature that is 18°C higher than that of PSP-I/PSP-I1 (78.6"C and 60.5 "C, respectively), and the calorimetric enthalpy changes of thermal denaturation are 439 and 660 kJ/mol for PSP-I/PSP-I1 and aSFP, respectively (MenCndez et al, 1995). Comparison of the surface potentials and interior packings of PSP-I/PSP-I1 and aSFP may provide clues to interpret the different biophysical and ligandbinding characteristics of these two spermadhesin molecules.…”
Section: Drr(i) = C ( L I ( K ) -( I ) L ) / E I ( K ) Where I mentioning
confidence: 99%